Bridging the gap : - Liemt, Gijsbert van (International Labour Office, 1988)
Contents: Economic and manufacturing growth of four NICs: The period up to 1980, The role of government in the process of industrialisation, The mixed economy in the industrial sector, Employment wages and income distribution,...